Orthokeratology for myopia control in Covid-19 era. Issue 8 (August 2020) - Morgan, Philip; Jones, Lyndon; Gifford, Kate
Abstract : Philip Morgan, Lyndon Jones and Kate Gifford evaluate considerations on using orthokeratology contact lenses for myopia control during the Covid-19 pandemic